The Global Movement for Human Rights Education - Flowers, Nancy (Radical Teacher, 2015)
An overview of the global movement for human rights education (HRE), its impetus, challenges, and contrasting developments in different regions of the world, focusing especially on Latin America, the Philippines, South Africa, the Middle East, and Europe. Seeks to put HRE in the USA into an international perspective, as well as to show the variety of goals that inspire HRE and how methodologies have evolved to meet specific regional and political cultures and needs.